DETERMINATION OF THE LEVEL OF PRIORITY IN THE AUDIT SCHEDULING FEATURES (Global Conference on Multidisciplinary Research and Innovation, 2026)
In the process of auditing the auditor, the sources that determine the content of users' economic decisions on the data that substantiate the composition of the subject funds and sources of their creation are considered important and they represent the composition of the level of importance. The importance level is used in auditing practice in accordance with the current standards No. 320 "Importance in planning the audit of financial statements" and No. 450 "Assessment of identified distortions in the course of the audit." However, these standards do not contain a clear methodology for determining and applying importance, as well as specific requirements for the level of importance.